SOCIAL INSTITUTION AND PROCESSES: A SOCIOLOGICAL DOMINANT - I. V. Petrova; A. V. Labudin (Дискурс)
The research format of the open state-social-personal system presents the results of the analysis of higher education conditions for the socialization of students. The definition of the important role of the spatial factor - research sociological education reveals the need to introduce a multifunctional management mechanism of the educational subsystem of society. The project features sociological intervention of processes at all levels of the system, which provides functional flexibility and gives focus on the goal-attainment. The possibility of introducing sociological support for the co-management of the system processes of the institutional environment for other institutions of society is demonstrated.